Authentic engagement: A conceptual model for welcoming diverse and challenging consumer and survivor views in mental health research, policy, and practice. (20th September 2019) - Daya, Indigo; Hamilton, Bridget; Roper, Cath
Abstract: As involvement of consumers/survivors in planning, delivery, and evaluation of services has increased, expectations of authentic and effective engagement, versus tokenism, have also risen. Different factors contribute to, or detract from, authentic engagement. Writing from mental health consumer/survivor and nursing positioning, respectively, we aim to redress the common problem of including only a narrow range of views and voices. This paper introduces a conceptual model that supports leaders in research, clinical, service, and policy roles to understand the necessity of engaging with a broader spectrum of consumer/survivor views and voices. The model draws on published consumer/survivor materials, making explicit diverse experiences of treatment and care and identifying the subsequent rich consumer/survivor advocacy agendas. We propose that strong co‐production is made possible by recognizing and welcoming consumer/survivor activist, facilitator, transformer, and humanizer contributions. The conceptual model forms the basis for a proposed qualitative validation project.